Identifikasi Kesiapan Unit Pelaksana Teknis Perpustakaan Universitas Sebelas Maret dalam Mendukung Akreditasi Internasional Program Studi - Utari, Sri; Anawati, Sri; Demartoto, Argyo (Direktorat Perpustakaan Universitas Islam Indonesia, 2024)
The aim of this research is to identify readiness, determine the supporting and inhibiting factors of the UNS Library in supporting the accreditation of international study programs. There has been a lot of research on the accreditation of university libraries, but research on the readiness of libraries to support the accreditation of international study programs is still limited. Qualitative research method with data collection using FGD and literature study. Discussion: The readiness of the UNS Library to support accreditation of international study programs includes having print and electronic collections, having various kinds of services, availability of regular budgets, infrastructure facilities, quality human resources, information literacy and library promotion. Supporting factors: Strategic building location; Adequate reading space and service hours; Adequate collection of books and e-journals; Active in organizing various literacy activities; Various social media are available for library promotion; Automation library, warehouse library; Large number of human resources; and Foreign Student Services. Inhibiting factors: Not having a programmer's library; Uneven competency of librarians; Lack of mastery of international languages for any staff; Lack of coordination between faculties/study programs that will receive international accreditation and the library; Unattractive room design; Limited space to store print collections; and Limited budget to organize library activities. Conclusion: There is a need to increase the supporting components of UNS Library Readiness in carrying out accreditation of international study programs.